Chronic ankle instability patients exhibit higher variability in lower extremity joint-coupling variability during drop vertical jumps. (23rd January 2020) - Herb, C.C.; Blemker, S.; Saliba, S.; Hart, J.; Hertel, J.
Abstract: Chronic ankle instability (CAI) has been associated with biomechanical alterations during landing tasks. While joint coupling differences have been reported during gait in patients with CAI, there is no known research assessing joint coupling during a drop-vertical jumping (DVJ). Joint coupling variability measure may provide information on the sensorimotor health of these patients. The purpose of this study was to compare lower extremity joint coupling variability during a DVJ between patients with CAI and controls. Twenty-eight young, active individuals (CAI:n = 14, Control:n = 14) participated in the study. A 3D motion capture system was used to collect kinematics during 15 drop-vertical jump trials. A vector coding analysis was used to assess the variability in the following joint couples: knee sagittal-ankle frontal, knee sagittal-ankle sagittal, hip frontal-ankle frontal, and hip frontal-ankle sagittal. The CAI group had higher joint coupling variability in hip frontal-ankle sagittal, knee sagittal-ankle frontal and knee sagittal-ankle sagittal planes both prior to and following ground contact during the drop vertical jumps. These changes indicate potential adaptations to the constraint of CAI and the task of the DVJ. Higher variability may reflect an attempt by the subjects to explore alternate movement strategies or reflect poor sensorimotor control strategies. Clinicians should consider the challenges of DVJ during rehabilitation as they create a unique task constraint.